2021
DOI: 10.1016/j.mjafi.2021.06.032
|View full text |Cite
|
Sign up to set email alerts
|

COVISHIELD (AZD1222) VaccINe effectiveness among healthcare and frontline Workers of INdian Armed Forces: Interim results of VIN-WIN cohort study

Abstract: Background On 16 Jan 2021, India launched its immunization program against COVID-19. Among the first recipients were 1.59 million Health Care Workers (HCWs) and Frontline Workers (FLWs) of the Indian Armed Forces, who were administered COVISHIELD (Astra Zeneca). We present an interim analysis of vaccine effectiveness (VE) estimates till 30 May 2021. Methods The VIN-WIN cohort study was carried out on anonymized data of HCWs and FLWs of Indian Armed Forces. The existing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 17 publications
(22 reference statements)
3
36
1
Order By: Relevance
“…Comparison with other studies is mentioned in Table 4. In our study, the median days between the second dose and being tested positive for SARS-CoV-2 was 65 days which is much longer than reported in all the previous studies, which ranged from 5 days or 47 days [9,12,15,16]. Also, none of the vaccinated HCWs who tested positive for SARS-CoV-2 were hospitalized, and there were no deaths, which in turn proves that vaccination reduces hospitalization by 100% which is more than the results observed in a study conducted in Scotland (88%) [18] and England (43%) [19].…”
Section: Resultscontrasting
confidence: 45%
See 2 more Smart Citations
“…Comparison with other studies is mentioned in Table 4. In our study, the median days between the second dose and being tested positive for SARS-CoV-2 was 65 days which is much longer than reported in all the previous studies, which ranged from 5 days or 47 days [9,12,15,16]. Also, none of the vaccinated HCWs who tested positive for SARS-CoV-2 were hospitalized, and there were no deaths, which in turn proves that vaccination reduces hospitalization by 100% which is more than the results observed in a study conducted in Scotland (88%) [18] and England (43%) [19].…”
Section: Resultscontrasting
confidence: 45%
“…The linear forecast (dotted line) graph (Figure 2), shows that the probability of getting infected in vaccinated HCPs is comparatively less than the unvaccinated group. Completing the full course of the vaccination decreased the risk of infection with the SARS-CoV-2 virus by 84.96% which is lower than the 91.8 -94.9% in the VIN-WIN cohort [12] and the study done by Benal JL et.al i.e, 89% (85% to 93%) [13].…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…respectively [9]. A large-scale study in India armed forces following completed Covishield vaccine revealed nearly 93% reduction in prevalence of Covid infections; and, reduction in COVID-related deaths by 98% [9]. Breakthrough infections were found to be related with COVID-19 variant of concern [10].…”
Section: Introductionmentioning
confidence: 99%
“…Victor et al had documented that the protective effect of covid vaccination in preventing infection, hospitalization, need for oxygen and ICU admission were 65%, 77%, 92% and 94% respectively[12]. VIN-WIN cohort study conducted among 1.59 million health care workers and frontline workers of Indian Armed Forces showed a 93% reduction in breakthrough infection following Covishield vaccination[13]. Ella et al[5], Voysey et al[4] had also documented the protective effect of the vaccine in preventing infection.…”
Section: Discussionmentioning
confidence: 99%